ANALISIS BIAYA PRODUKSI DAN HARGA JUAL DALAM MENINGKATKAN LABA HOME INDUSTRY (STUDI KASUS PADA KELURAHAN NANGALIMANG) - Yustina Nona Nadia, Maria; Herdi, Henrikus; Maria Dilliana, Siktania (Universitas Nusa Nipa Maumere, 2025)
This study aimend to examine the influence of environmental, environmental costs, and enviromental disclosure on profitability in pharmaceutical sub-sector manufacturing companies listed on the indonesia Stock Exchange (IDX). This research employed a quantitative method with purposive sampling techniques. The study used a sample of 11 companies that met the predetermined criteria. The source of data used in this research was secondary data obtained from documents accessed through the official website of the indonesia Stock Exchange (IDX) at www.idx.co.id. The analytical method applied was multiple linear regression analysis. The results indicated that environmental performance (X1) had a negative and significant relationship between PROPER and ROA, environmental costs (X2) had a negative and significant relationship with ROA, and environmental disclosure (X3) had a negative but insignificant relationship with ROA